Comparative performance analysis of TCP-based congestion control algorithms. (2016) - Patel, Sanjeev; Rani, Kritika
Congestion control is a challenging problem for us. We tried to analyse the end-to-end congestion control algorithms, i.e., TCP Tahoe, TCP Reno, TCP Newreno, TCP Veno, etc. In the literature, TCP implements a window-based flow control mechanism which leads to vary the window size within a range. Older TCP designed assuming packet loss is always inferred due to congestion on link which leads to degradation of performance in wireless networks where random loss occurred due to transmission error or noise. This well-known problem affects on TCP performance. TCP Veno has been successfully proposed to deal with random loss efficiently and its performance is discussed in the literature. This paper evaluates the complex model for different performance parameters, i.e., throughput, queuing delay, goodput, etc. In addition, we have also proposed new performance metric to measure the network performance. We also tried to study and compare the analytical results with simulated data at different levels of loss rate.